RESERVOIR MODELING OF TALANG AKAR FORMATION, PEPO FIELD, SOUTH SUMATRA BASIN - ONGGA RAHMAT (NIM : 12012081), ISMI
The research area is located on the Pepo Field, southern Sumatra Basin. This field is an old field that hydrocarbon production has decreased. The main layers producing hydrocarbons in this field are layers Upper Talang Akar Formation reservoir. Modelling undertaken include modeling facies, porosity, permeability, NTG, Water Saturation. In this study also analyzes sequence stratigraphy, facies analysis, the correlation between wells, and petrophysical calculations. Based on studies it is known that Upper Talang Akar Formation deposited in the transition environment. Deltaic environment can be a transition, the beach to the sea shallow. Transitional environment can have different depositional facies. The depositional facies affect the formation and distribution of the reservoir. Modeling is one method to determine the distribution of the reservoir. Based on the analysis of sequence stratigraphy, the study zone is located between SB0 and MFS2. From SB0 to MFS2 are FS01, FS02, FS03, FS04, MFS1, SB1, and FS 11. Based on facies analysis note that the research field consists of tidal sand bar, tidal channels, mud flats, and the Marine shale. Distribution reservoir facies distribution is influenced by the relative trending NNESSW. Reservoir in the study zone has an average porosity of 15:56%. Hydrocarbon reserves calculation yields an estimate of 10 MMSTB.